Increase of tropical seabirds (Sula) in the California Current Ecosystem with warmer ocean conditions - Tamara M. Russell; David M. Pereksta; James R. Tietz; Maria Vernet; Jaime Jahncke; Lisa T. Ballance (Frontiers in Marine Science)
Climate change is impacting marine ecosystems through physical changes (e.g., increased marine heatwaves, long-term warming) that can manifest biologically at all trophic levels. In the California Current Ecosystem (CCE), a productive and economically important eastern boundary upwelling system, the effects of these physical changes are observed throughout the region from Mexico to Canada. We investigated range expansions into the CCE and correlations with the environment for a group of tropical/sub-tropical seabirds, widely recognized as ecosystem indicators. We assessed changes in the abundance (2002-2022) of five species from the genus Sula (Cocos, Blue-footed, Red-footed, Masked, and Nazca Boobies), using a novel compilation of four data sources and investigated potential relationships with the environment. All five species increased in abundance within the CCE by 692-3015% after the extreme marine heatwaves that began in late 2013, and all species, with the exception of Blue-footed, exhibited a northward range expansion by as much as 6.8 degrees latitude and increased range area of 235-1013%. Furthermore, the increased presence of all species except Masked and Nazca Boobies correlated with warmer conditions around Baja California, Mexico, one month prior to their occurrence northward. Our results document the increase of these large bodied, tropical species and a tropical shift in the predator community of the CCE, which mirrors changes that occurred there during the last extreme global warming period on Earth, the Miocene. As marine heatwaves are projected to increase in frequency and intensity, in addition to long-term warming, we hypothesize that these species will continue to expand their range northward and increase in abundance in this upwelling ecosystem.